Intervention effects from a social marketing campaign to promote HPV vaccination in preteen boys - Cates, Joan R. (2014)
OBJECTIVES: Adoption of human papillomavirus (HPV) vaccination in the US has been slow. In 2011, HPV vaccination of boys was recommended by CDC for routine use at ages 11–12. We conducted and evaluated a social marketing intervention with parents and providers to stimulate HPV vaccination among preteen boys. METHODS: We targeted parents and providers of 9–13 year old boys in a 13 county NC region. The 3-month intervention included distribution of HPV vaccination posters and brochures to all county health departments plus 194 enrolled providers; two radio PSAs; and an online CME training. A Cox proportional hazards model was fit using NC immunization registry data to examine whether vaccination rates in 9–13 year old boys increased during the intervention period in targeted counties compared to control counties (n=15) with similar demographics. To compare with other adolescent vaccines, similar models were fit for HPV vaccination in girls and meningococcal and Tdap vaccination of boys in the same age range. Moderating effects of age, race, and Vaccines for Children (VFC) eligibility on the intervention were considered. RESULTS: The Cox model showed an intervention effect (β=0.29, HR=1.34, p=.0024), indicating that during the intervention the probability of vaccination increased by 34% in the intervention counties relative to the control counties. Comparisons with HPV vaccination in girls and Tdap and meningococcal vaccination in boys suggest a unique boost for HPV vaccination in boys during the intervention. Model covariates of age, race and VFC eligibility were all significantly associated with vaccination rates (p<.0001 for all). HPV vaccination rates were highest in the 11–12 year old boys. Overall, three of every four clinic visits for Tdap and meningococcal vaccines for preteen boys were missed opportunities to administer HPV vaccination simultaneously. CONCLUSIONS: Social marketing techniques can encourage parents and health care providers to vaccinate preteen boys against HPV.